A Pragmatic Analysis Of Euphemisms In The English Translation Of Holy Quran By Yusuf Ali - Thrisyarni, Yesy Yuli; , Drs. Maryadi M. A.; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
The objectives of the study are (1) to describe the type of euphemisms used in the English translation of Holy Qur‟an and their replacement, (2) to describe the referent of euphemisms used in the English translation of Holy Qur‟an, and (3) to describe the intention of euphemisms used in the English translation of Holy Qur‟an. The type of this research is qualitative research. In collecting the data, the writer uses documentation method by selecting the euphemism which can be found in English translation of Holy Quran by Yusuf Ali. To achieve the type of euphemism, the writer classifiesdata based on theory agreed upon Williams (1975); Shipley (1977); Rawson (1983); Neaman & Silver (1983); Allan & Burridge (1991). To achieve the referent, the writer uses the theory of Nida (1975). To dig the intention of euphemisms the translation English translation of Holy Quran by Yusuf Ali chapter The Heifer by occupying the theory of Speech act of Austin (1962). The result of the study shows that regarding to the (1) types of euphemism, the writer found the types of euphemism as follows: 1) 16semantic change (80%), specifically, they are 7 semanticshifts (35%), 2 indirections (10%), 2 understatements (10%), 2 widening(10%), 2 liotes (10%), 1 metaphoricaltransfer (5%), and 4 circumlocutions (20%); and 2) 4 circumlocation(20%). (2) referents are: extensionalist (see words in their contexts) (90%) and intensionalist (analyze the contour of words as in componential analysis) which is contiguity (10%). (3) The intentions are representative of asserting(10% usage) andrepresentative of recalling(5% usage),directives of requesting(5% usage),directives of forbidding (15% usage) and directives of commanding (40% usage), commissives of threatening (15% usage), declarations of declaring war (5% usage) and declarations of excommunicating (5% usage), and there is no expressive.